Petroscirtes pylei, a new saber-toothed blenny from the Fiji Islands (Teleostei: Blenniidae) - Smith-Vaniz, William F. (Zootaxa, 2005)
Petroscirtes pylei is described from three specimens, 20.3–40.9 mm SL, obtained from a deepwater reef off Suva, Viti Levu, Fiji Islands. It is distinguished from all other congeners by its color pattern, including the presence of two dark body stripes, the lower one broadly extending onto the anal fin, and the dorsal fin with a broad, dark basal stripe, superimposed by a conspicuous white spot centered on the 4th spine. Among Petroscirtes, only the new species and P. springeri typically have 12 dorsal-fin spines but they are not closely related. The holotype was collected in 104–110 m, the second deepest depth record for a species of Petroscirtes. Discovery of this new species, and an apparently second new deep-water Petroscrites (uncollected), at a different Fijian reef indicates that our knowledge of the biodiversity of this habitat and of the saber-toothed blennies is very incomplete.